T-S Fuzzy Model Based Output Feedback Tracking Control with Control Input Saturation - Yu, Y.; Lam, H.; Chan, Kit Yan (IEEE, 2018)
This paper investigates the output feedback tracking control for a fuzzy-model-based (FMB) control system when the control input is saturated, where the FMB is developed based on a T-S fuzzy model and a fuzzy controller. The controller is employed to close the feedback loop and generate the system to trace the trajectory of the states of a stable reference model subject to H∞ performance. To enhance the fuzzy controller design flexibility, the number of rules and premise membership functions can be adjusted. Stability analysis for the FMB control system is performed based on Lyapunov stability theory. To address the control input saturation problem, linear sectors are created by local linear upper and lower bounds to include the possible control area. Hence, the nonlinear saturation problem can be tackled by the stability analysis of linear sectors. The membership-functions-dependent technique is used to bring the information and address the nonlinearity of embedded membership functions into the stability analysis. The numerical simulation example demonstrates the effectiveness of the proposed approach and discusses the effect of H∞ performance and control input saturation rate according to the tracking result.